2000
DOI: 10.1366/0003702001950030
|View full text |Cite
|
Sign up to set email alerts
|

Study of Solution Calibration of NIST Soil and Glass Samples by Laser Ablation Inductively Coupled Plasma Mass Spectrometry

Abstract: A method for the determination of trace element concentrations by laser ablation inductively coupled plasma mass spectrometry (ICP-MS) using solution calibration and an internal standard has been studied and evaluated by analyzing NIST soil and glass samples. In most cases, the measured element concentrations were within ±10% of the certified values. The internal standard was chosen on the basis of investigations of the proper signal intensity of certain isotopes and the homogeneity of their distribution in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Bi et al [67] Poor accuracy was observed for Cu and Ni in soil samples, whereas good results were obtained for these elements in glass samples. The cause of the error was believed to be due to the heterogeneity of elements in the sample.…”
Section: Dual Introduction (Sample-standard)mentioning
confidence: 95%
“…Bi et al [67] Poor accuracy was observed for Cu and Ni in soil samples, whereas good results were obtained for these elements in glass samples. The cause of the error was believed to be due to the heterogeneity of elements in the sample.…”
Section: Dual Introduction (Sample-standard)mentioning
confidence: 95%
“…Differences in the ablation behavior of analytes known as elemental fractionation can be diminished by internal standardization in combination with a suitable binder [9]. Few applications have been published on laser ablation of soils either with ICP-AES [5,10] laser-induced breakdown spectroscopy [11] or ICP-MS [12,13,14]. In contrast to rocks, ores, or minerals, soils represent more complicated matrices because of significant and variable content of organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…The following approaches can be presented as typical examples: i) closely matrix-matched calibration with solid reference materials in LA-ICP-AES of geochemical samples [3] and soils [5]; ii) matrix-matched calibration with uncontaminated natural matrix spiked with analytes, both as solutions and solid certified reference materials in the LA-ICP-MS of road sediments [6] and in the LA-ICP-AES analysis of agricultural soils [6]; iii) liquid-solid calibration in the analysis of soils by LA-ICP-AES [5] and LA-ICP-MS [14].…”
Section: Introductionmentioning
confidence: 99%
“…For lead the authors encountered some not specied problems: the result differs 35% from the certicate. 33 The determined recovery of the results with respect to the certicate became worse with increasing mass of the analyte element. In our work, using the solid sample itself as the reference material, no signicant dependence of the recovery on the element mass was observed (Pb in SRM 612: 7%).…”
Section: Calculation Of Mass Fractionmentioning
confidence: 97%